Influencing Factors of Patients’ Choice in the Online Medical Markets: A Systematic Review - Ansalmus Oron; Ernawaty Ernawaty (Universitas Malahayati, 2024)
Background: The telemedicine system has created a new and important way for patients to find a doctor. This research aims to identify the influencing factors of patients’ choice in the online medical market using a systematic review study.Methods: Articles published in the last 5 years in Proquest, Google Scholar, and PubMed databases were systematically reviewed. Sixteen articles that met the inclusion and exclusion criteria were selected for further review. Findings regarding the influencing factors of patients’ choice in the online medical were systematically synthesized.Results: Sixteen articles explore seven main factors of patient choice in the online medical market such as physician factors, service quality, location, trust, WoM, patient perception and illness severity.Conclusions: Our study recommends that doctors should improve their medical skills, manners, appealing channel for health, actively publicize, increase the number of online consultations appealing channel for health, the frequency of updating the doctor's quality information and show their professional level to provide better service. The quality of online service are equally important to online doctor-patient trust and thus improve their influence.